Spread of quarantine plant pests in Ukraine - Yu. Holiachuk; H. Kosylovych (Карантин і захист рослин)
Goal. Of article is analyse of spreading dynamics of insect species with the quarantine status for Ukraine territory based on data of the State Service of Ukraine on Food Safety and Consumer Protection.